Analysis of The Existing Condition of Cibangreng Lake Lebak Regency - Gemilang, Meysa Cahya; Taufik, Isvan; Sudrajat, Endang (Lembaga Pengembangan Kinerja Dosen, 2025)
Lakes have strategic potential and benefits that are beneficial both ecologically and economically, including as part of a region's water management system, reservoirs, water catchment areas, inland fisheries cultivation locations, part of irrigation systems, and potential as tourist attractions. Most research on lakes in Indonesia is conducted by analyzing water quality and tourism conditions in the lake. Meanwhile, this study will discuss the analysis of existing conditions by considering the type of land use in the Situ Cibangreng area, Lebak Regency, and the analysis of indications of the Situ Cibangreng area in Lebak Regency, Banten Province, West Java. The method used in this study is qualitative analysis. During the data collection stage, the research team will explore the study area through field observations to obtain a general picture of conditions within the Situ area. The survey method is carried out using Topographic Measurement Methods, Geographic Information Systems (GIS), 3.2.2 Aerial Photography with Drones/UAVs and using Spatial Data Analysis. Based on field observations, Situ Cibangreng is located in Muaradua village, Cikulur district. There are several types of land use in this area, including: 1) built-up land use: housing and road networks; 2) use of non-built land, including mixed gardens and food crop areas (rice fields). The aerial mapping results provide a detailed picture of the existing conditions of Situ Cibangreng, including inundation boundaries, surrounding land use patterns, and indications of changes in the lake's morphology. This data serves as a crucial basis for hydro-logical analysis, lake normalization planning, and zoning of the boundary area to maintain the ecological function and sustainable capacity of Situ Cibangreng.